2021
DOI: 10.1002/hrdq.21467
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between talent management and employee job‐related outcomes: The case of the Indian manufacturing industry

Abstract: This study examined the relationship between talent management (TM) and employee job‐related outcomes in the Indian manufacturing setting. TM practices included talent acquisition, talent development, talent engagement, and talent retention. Employee job‐related outcomes of this study included intent to stay, job engagement, affective commitment, job satisfaction, and employee competency. This study used the social exchange theory and a resource‐based view as the theoretical underpinnings for the proposed TM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 157 publications
1
4
0
Order By: Relevance
“…In the regression analysis in this study, it was found that TM significantly and positively affected nurses' intrinsic satisfaction and extrinsic satisfaction, job satisfaction, affective commitment, normative commitment, and continuance commitment. Non-nursing previous studies, similar to the current study, found that TM affected job satisfaction positively (Alparslan & Saner, 2020;Dalal & Akdere, 2021;Tarakçı & Öneren, 2018) and significantly (Alparslan & Saner, 2020;Dalal & Akdere, 2021;Hafez et al, 2017), and that it affected the job satisfaction subdimensions of intrinsic satisfaction and extrinsic satisfaction significantly (Serim Bahadınlı, 2013). A study conducted in the academic field in Turkey reported that TM significantly and positively affected affective commitment, normative commitment, continuance commitment, and organizational commitment (Tarakçı & Öneren, 2018).…”
Section: F I G U R E supporting
confidence: 82%
“…In the regression analysis in this study, it was found that TM significantly and positively affected nurses' intrinsic satisfaction and extrinsic satisfaction, job satisfaction, affective commitment, normative commitment, and continuance commitment. Non-nursing previous studies, similar to the current study, found that TM affected job satisfaction positively (Alparslan & Saner, 2020;Dalal & Akdere, 2021;Tarakçı & Öneren, 2018) and significantly (Alparslan & Saner, 2020;Dalal & Akdere, 2021;Hafez et al, 2017), and that it affected the job satisfaction subdimensions of intrinsic satisfaction and extrinsic satisfaction significantly (Serim Bahadınlı, 2013). A study conducted in the academic field in Turkey reported that TM significantly and positively affected affective commitment, normative commitment, continuance commitment, and organizational commitment (Tarakçı & Öneren, 2018).…”
Section: F I G U R E supporting
confidence: 82%
“…Investing in employees' training and career growth can have a significant positive impact on an organisation. The human resource department's role extends beyond managing the workforce to nurturing the talents and skills of employees, creating a productive and prosperous work environment [ 79 ]. By fostering ambidexterity in employees, organisations can create a more agile and innovative culture, which can lead to improved performance and a competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a priority for the government to accelerate reform in providing a clean, efficient, and effective government through implementing talent management at the central and regional levels. Most of the references defined talent management as managing employees in the organization with the aim of (1) finding the best employees, (2) attracting the best people to enter the organization, (3) retaining the best employees to continue to perform according to organizational needs (Dalal & Akdere, 2021;Kabwe & Tripathi, 2020;Schreuder & Noorman, 2019). Not much research and publication discuss the implementation of talent management in government institutions, especially in local government.…”
Section: Statistics On State Civil Apparatus (Asn) Data From the Stat...mentioning
confidence: 99%